Diversity and Inclusion in the Workplace : Ethical Considerations - Miliukova, Elizaveta; Kučera, Dušan; Cejthamr, Václav, 1964-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
Diversity and inclusivity in the workplace are important components of modern business ethics, reflecting the integration of people from different walks of life based on race, nationality, culture, religion, gender, age, abilities, sexual orientation and lifestyle. Inclusivity ensures the harmonious collaboration of these different groups within organizational teams. As the global landscape changes, enterprises must maintain the ability to adapt, take into account trends and expand knowledge to ensure sustainable growth. This article examines the crucial role of diversity in the modern business environment. The study highlights the relationship between diversity and success in the market. It analyzes practical strategies to promote and develop diversity based on the examples of successful corporations such as Microsoft and Henkel. By conducting a comparative analysis, the study identifies effective methods and approaches for forming a diverse workforce and achieving organizational goals. This study highlights the need for businesses to prioritize diversity and outlines practical steps to implement it. Through this research, the article contributes to the discussion of diversity and inclusivity in business ethics, providing valuable information to organizations seeking to increase diversity in the workplace and create an inclusive environment.
Vedoucí práce: Dušan Kučera
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses